2015
DOI: 10.1111/cbdd.12664
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of MiR‐122 via Trichostatin A Treatments in Hepatocyte‐like Cells Derived from Mesenchymal Stem Cells

Abstract: The miR-122 is a tissue-specific miRNA; its expression is abundant in liver. MiR-122 upregulation is crucial for differentiation, functionality, and maintenance of differentiated phenotype in hepatocytes. The improving effects of trichostatin A (TSA) on hepatic differentiation have been reported previously. The aim of this study was to determine whether TSA can affect the expression of miR-122 in hepatocyte-like cells (HLCs) generated from human adipose tissue-derived mesenchymal stem cells (hAT-MSCs). The hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…DNA methylation as an epigenetic alteration commonly occurs at 5′cytosine (5′C) of pyrimidine cycle and plays a key role in genome regulation and development (Bird, ; Holliday & Pugh, ; Momparler & Bovenzi, ). Apart from its role in physiological functions, aberrant DNA methylation is related to the inappropriate transcriptional silencing of genes (Issa, ; Molavi et al, ), that provides an advantage for several diseases such as diabetes, heart disease, autoimmune, and aging‐related diseases (Egger, Liang, Aparicio, & Jones, ; Irier & Jin, ; Jayaraman, ; Movassagh, Vujic, & Foo, ; Robertson, ) and many types of cancer including colorectal (Hughes et al, ; Samowitz, ; Toyota et al, ), lung (Marsit et al, ; Shigematsu et al, ), liver (Alizadeh et al, ; Shen et al, ), and breast cancer (Fang et al, ). In contrast to normal cells, cancer cells globally exhibit a lower levels of 5‐methylcytosine in the genome, but simultaneously a higher levels of methylation in tumor suppressor genes promoters (Jones & Baylin, , ).…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation as an epigenetic alteration commonly occurs at 5′cytosine (5′C) of pyrimidine cycle and plays a key role in genome regulation and development (Bird, ; Holliday & Pugh, ; Momparler & Bovenzi, ). Apart from its role in physiological functions, aberrant DNA methylation is related to the inappropriate transcriptional silencing of genes (Issa, ; Molavi et al, ), that provides an advantage for several diseases such as diabetes, heart disease, autoimmune, and aging‐related diseases (Egger, Liang, Aparicio, & Jones, ; Irier & Jin, ; Jayaraman, ; Movassagh, Vujic, & Foo, ; Robertson, ) and many types of cancer including colorectal (Hughes et al, ; Samowitz, ; Toyota et al, ), lung (Marsit et al, ; Shigematsu et al, ), liver (Alizadeh et al, ; Shen et al, ), and breast cancer (Fang et al, ). In contrast to normal cells, cancer cells globally exhibit a lower levels of 5‐methylcytosine in the genome, but simultaneously a higher levels of methylation in tumor suppressor genes promoters (Jones & Baylin, , ).…”
Section: Introductionmentioning
confidence: 99%
“…44,45 miR-122 is a well-studied microRNA playing an important role in regulating hepatocyte development and differentiation 46 ; a very recent study found that TSA administration during hepatogenic differentiation of hMSCs resulted in higher expression levels of miR-122 facilitating reprogramming efficiency providing a potential underlying molecular regulatory cue of hMSC-to-liver differentiation. 47 A previous study has shown that miR-122 expression is essential for HCV proliferation in host cells after infection. 48 Mechanistically, several reports revealed that a specific interaction between the seed domain of miR-122 and the complementary sequences in the 5′UTR of HCV RNA is essential for the enhancement of translation and replication of the HCV genome.…”
Section: Discussionmentioning
confidence: 99%
“…HCV infection is a multi‐step event, and it was shown that liver‐specific microRNA miR‐122 is essential for HCV replication . miR‐122 is a well‐studied microRNA playing an important role in regulating hepatocyte development and differentiation; a very recent study found that TSA administration during hepatogenic differentiation of hMSCs resulted in higher expression levels of miR‐122 facilitating reprogramming efficiency providing a potential underlying molecular regulatory cue of hMSC‐to‐liver differentiation . A previous study has shown that miR‐122 expression is essential for HCV proliferation in host cells after infection .…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies of the effects of histone deacetylase inhibitors (HDACis), such as trichostatin A and dimethylsulphoxide, on hepatocyte differentiation. 7884 HDACis have a broad range of effects, including up-regulating expression of LETFs, such as HNF4A, HNF1A, CEBPA, and FOXA2, 79 and increasing transcriptional activity by binding to promoter regions of CYP genes and glucose-6-phosphate dehydrogenase. 8082 Additionally, HDAC is regulate liverspecific expression of MIR122.…”
Section: Strategies To Promote Hepatocyte Differentiation and Maturationmentioning
confidence: 99%